Hepatitis C recurrence: the Achilles heel of liver transplantation. Issue 1 (30th December 2013) - Howell, J.; Angus, P.; Gow, P.
Abstract Hepatitis C virus (HCV) infection is the most common indication for liver transplantation worldwide; however, recurrence post transplant is almost universal and follows an accelerated course. Around 30% of patients develop aggressive HCV recurrence, leading to rapid fibrosis progression (RFP) and culminating in liver failure and either death or retransplantation. Despite many advances in our knowledge of clinical risks for HCV RFP, we are still unable to accurately predict those most at risk of adverse outcomes, and no clear consensus exists on the best approach to management. This review presents a critical overview of clinical factors shown to influence the course of HCV recurrence post transplant, with particular focus on recent data identifying the important role of metabolic factors, such as insulin resistance, in HCV recurrence. Emerging data for genetic markers of HCV recurrence and their usefulness for predicting adverse outcomes will also be explored.